Formation of professional engineering foreign language communicative competence - Овсянко Г. В. (My University, 2023)
It is considered the question of formation of foreign language communicative competence of future engineers. It is empha-sized the need and importance of studying the terminological vocabulary in the process of mastering a foreign language for special purposes by students of engineering specialties at a technical university. The stages of formation of communicative competence are analyzed and the role of professionally oriented texts in this process is determined. The necessity of constantly searching for new opportunities and methods for forming and improving the communicative competence of future engineers is indicated.
Овсянко, Г. В. Formation of professional engineering foreign language communicative competence / Г. В. Овсянко // The 46th Intern. scientific and practical conf. "Humanity and Science". – Chicago : Primedia E-launch LLC USA , 2023. – P. 63–66.